Pemberdayaan Masyarakat dalam Menjaga Kebersihan melalui Pengelolaan TPS di Desa Lubuk Bayas, Kecamatan Perbaungan melalui Program KKN Kelompok 01 UNIVA Medan - Hasnah Siahaan; Mhd Fachry R Srg; Nuranisa Nuranisa; Nazlia Adinda Putri; Chainur Azmi; Wahyu Munandar (Pusat Riset dan Inovasi Nasional, 2025)
The findings of this study indicate that work environment, job satisfaction, and motivation simultaneously have a significant effect on the commitment of teachers and staff at Petukangan Selatan 01 Public Elementary School. This shows that a conducive work environment, such as adequate facilities, supportive colleagues, and a comfortable atmosphere, can increase the sense of belonging and loyalty among employees. Job satisfaction, which includes aspects such as fairness in rewards, recognition of achievements, and appropriate workloads, also contributes to strengthening work commitment. In addition, motivation, both intrinsic and extrinsic, plays a central role in encouraging employees to perform their duties with responsibility and enthusiasm. These findings also reinforce the importance of creating a balance between external factors (such as work environment) and internal factors (such as motivation and job satisfaction) to achieve strong commitment. Therefore, the implication of this research is that school management needs to continuously improve working conditions, develop fair reward systems, and provide opportunities for career development. By doing so, the commitment of teachers and staff can be maintained and even enhanced, which in turn will support the achievement of school goals more effectively.